Enhancement of combustion performance and emission control in Bauhinia malabarica biodiesel-diesel blends using aluminium oxide nanoparticles and electrostatic precipitators - Suresh Vellaiyan (Cleaner Engineering and Technology)
This study investigates the enrichment of combustion performance and emission features of Bauhinia malabarica biodiesel (BMB)-diesel mixtures through the addition of aluminium oxide (Al2O3) nanoparticles and the use of electrostatic precipitators (ESPs) to mitigate nanoparticle emissions. Different volume concentrations of BMB were combined with conventional diesel fuel (CDF), and 100 ppm of Al2O3 was dispersed into 30 % BMB-CDF blends using ultrasonication with a surfactant. The combustion analysis exposed that the addition of BMB to CDF reduced in-cylinder pressure while increasing net heat release and advancing the crank angle for peak values. The 30 % BMB blend led to a drop in brake thermal efficiency (BTE), with a corresponding upsurge in brake-specific fuel consumption (BSFC) and nitrogen oxides (NOx) emissions of 10.4 %, 11.3 %, and 10.9 %, respectively. However, formations of hydrocarbons (HC), carbon monoxide (CO), smoke, and particulate matter (PM) decreased by 14.3 %, 6.3 %, 11.1 %, and 12.5 %, respectively. The incorporation of Al2O3 nanoparticles improved BTE by 5.2 % and reduced BSFC, HC, CO, NOx, and smoke by 4.2 %, 13.7 %, 14.9 %, 5.8 %, and 15.5 %, respectively. Although PM emissions increased by 47.2 % with the nanoparticle-enriched blend, integration of the ESP effectively captured exhaust nanoparticles, reducing PM emissions by 54.2 %. This study reveals the potential of Al2O3 nanoparticle-enriched BMB mixtures in enlightening combustion performance and dropping most emissions, with ESP serving as an effective tool for controlling nanoparticle emissions.